PENGARUH PROFITABILITAS, LIKUIDITAS, DAN KEPEMILIKAN INSTITUSIONAL TERHADAP STRUKTUR MODAL - Maulana, Yasir; Aziz, Muhhammad Nur (Bisnis-Net, 2024)
This research aims to test and analyze the influence of profitability, liquidity and institutional ownership on capital structure. The population in this research are property and real estate sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the 2010-2019 period. Based on the purposive sampling method, 170 data were obtained from 17 property and real estate companies listed on the Indonesia Stock Exchange (BEI) during the 2010-2019 period. The analysis method uses panel data regression analysis, classical assumption testing and hypothesis testing. The research results show that 1) Profitability Ratios measured using ROA have a negative and significant effect on Capital Structure, 2) Liquidity Ratios measured using CR have a negative and significant effect on Capital Structure, 3) Institutional Ownership Ratios measured using KI have a positive and significant effect on Capital Structure. Meanwhile, simultaneously Profitability, Liquidity and Institutional Ownership influence Capital Structure.